The Risk-Taking Attitude of Student towards Mathematics through Inquiry-Based Open-Ended Learning - Yatha Yuni; Fiki Alghadari (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research was to know students' achievement and improvement risk-taking attitudes in grade 7 at Madrasah Tsanawiyah in Bekasi City towards mathematics through Inquiry-Based Open-Ended (IBOE) learning. This research is quantitative research with the research design Non-equivalent Pre and Post-test Control-Group Design. There are 156 students as a sample. It was taken using the purposive sampling technique from two Madrasah Tsanawiyah (MTs). Seventy-seven students in the experimental class (IBOE) and 79 students in the control class (Direct Learning: DL). They were grouped according to previous mathematics abilities (level high, medium, and low).  The instrument used was a questionnaire consisting of 17 valid statements adopted from the Domain-Specific Risk-Taking (DOSPERT) scale. The results of this research were reviewed based on early mathematical skills, achievement of the process of building a risk-taking attitude for MTs students. Students who received IBOE learning were no better than students who received DL.  Meanwhile, based on the early mathematical skills, students who increase in building a risk-taking attitude received IBOE learning was better than students who received DL.